Desenvolvimento de ELISA para o Diagnóstico da Neosporose - Pinheiro, Amanda Fernandes (2010)
The neosporosis is a disease caused by intracellular protozoa Neospora caninum, which is of great importance, especially in cattle, because it may cause abortion in infected animals, causing big economic losses for the cattle industry of many countries in the world. In the present study it was reported the expression, purification, and characterization of the protein NcSRS2 of N. caninum in the methylotrophic yeast Pichia pastoris. The gene ncsrs2 was cloned in the vector of expression pPICZαB, followed by the integration in the genome of yeast. The recombining protein NcSRS2 was shown in the supernatant of the culture, where later it was concentrated and purified. An indirect immunoenzymatic assay (ELISA) was developed, using seronegative and seropositive of cattle and sheep, naturally field-infected. It showed that the recombinant protein presented the antigenic characteristics of native protein, which allowed its recognition by the blood serum of different species of animals with neosporosis. The results were compared with the indirect immunofluorescence (IFI). The diagnosis test ELISA- NcSRS2 described in the present work is a specific and sensitive method for the detection of N. caninum in cattle and sheep. The results indicate that the recombinant protein produced in this work, can be used for the development of diagnosis methods with low-cost production, and in industrial scale, because they are necessary and important for the introduction of proper controlling measurements for this parasitosis in cattle flocks.